Hypothyroidism following immunotherapy predicts more postoperative complication in oral squamous cell carcinoma - Wenwen Zhang; Ping Lu; Xing Li; Qigen Fang (BMC Cancer)
Abstract Objective To evaluate the impact of hypothyroidism that develops following immunotherapy on surgical outcomes in patients diagnosed with oral cancer. Methods Patients with surgically treated oral cancer following neoadjuvant immunochemotherapy were retrospectively enrolled. Impact of hypothyroidism on postoperative complication were analyzed. Results In total, 303 patients were enrolled. In comparison to patients with normal thyroid function, patients with subclinical or overt hypothyroidism did not exhibit a significantly increased risk of surgical site infection, but both conditions were associated with a higher risk of fistula formation and wound debridement. The cohort suffering from subclinical hypothyroidism exhibited odds ratios (ORs) of 1.88 [95% confidence interval (CI): 1.12–5.47] for fistula development and 1.95 [95% CI: 1.27–6.98] for wound debridement. Patients with overt hypothyroidism had a 2.03-fold higher risk of fistula formation (95% CI: 1.35–6.24) and a 2.17-fold higher risk of wound debridement (95% CI: 1.20–7.53). The rate of wound debridement escalated to 40.0% when both hypothyroidism and diabetes were present simultaneously; in contrast, it diminished to 20.0% in cases of isolated hypothyroidism, 12.1% in individuals with diabetes alone, and a mere 5.2% in patients devoid of both conditions. The incidence of fistula formation was most pronounced in patients with coexisting diabetes and hypothyroidism, followed closely by 6.7% in those with solely hypothyroidism. The occurrence of fistulas was remarkably rare among patients with only diabetes or those lacking both factors. Conclusions Hypothyroidism induced by neoadjuvant immunotherapy exerts a considerable negative impact on the formation of fistulas and wound debridement in patients with locally advanced oral cancer, an effect that may be exacerbated by the presence of diabetes.